2018
DOI: 10.1080/13102818.2018.1480421
|View full text |Cite
|
Sign up to set email alerts
|

Comparative identification and evolutionary relationship of fatty acid desaturase (FAD) genes in some oil crops: the sunflower model for evaluation of gene expression pattern under drought stress

Abstract: Can & Rahmi Cetinkaya (2018) Comparative identification and evolutionary relationship of fatty acid desaturase (FAD) genes in some oil crops: the sunflower model for evaluation of gene expression pattern under drought stress, Biotechnology &

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 52 publications
4
10
0
Order By: Relevance
“…To date, stearoyl-ACP desaturase is the only identi ed soluble desaturase. The phylogenetic tree and the type of clustering of FAD proteins are consistent with the other plants, including sun ower [10], cucumber [43], and soybean [34]. Each cluster had similar amino acid compositions, and it can be concluded that the phylogenetic distribution of wheat FAD proteins is related to their motif contents.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…To date, stearoyl-ACP desaturase is the only identi ed soluble desaturase. The phylogenetic tree and the type of clustering of FAD proteins are consistent with the other plants, including sun ower [10], cucumber [43], and soybean [34]. Each cluster had similar amino acid compositions, and it can be concluded that the phylogenetic distribution of wheat FAD proteins is related to their motif contents.…”
Section: Discussionsupporting
confidence: 69%
“…In the current study, it was found that three genes on chr6A (TaFAD2.1-3), four genes on chr6B (TaFAD2.4-7), and four genes on chr6D (TaFAD2. [8][9][10][11] are the result of tandem duplication. Likewise, threes genes on chr2A (TaFAB2.1-3), chr2D (TaFAB2.9-11), chr5B (TaFAB2.…”
Section: Gene Location On a Chromosome Gene Duplication And Selectimentioning
confidence: 99%
“…For instance, the amino acid length between His-box 2 and His-box 3 was 111 or 171 in TaFAD2. [1][2][3][4][5][6][7][8][9][10][11]156 in TaFAD6.1-2, 162 in TaFAD3.1-6, 163 in TaFAD7.1-3 and TaFAD8.1-3, 173 in TaSLD1-3, and 127 in TaDES1-3. The exception was the TaFAD4 cluster, in which this length was only 25 amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…FADs are important to determine the quality of edible oils [9]. They have been attracted more attention due to their ability to adjust the level of unsaturated fatty acids to increase the quality of these oils and plant resistance against various stresses including drought, salt, heat, cold, and pathogen [10][11][12][13]. For instance, the cell membrane is the primary site for cold-induced injury and the melting temperature of the unsaturated fatty acids is less than saturated fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA was extracted using a Trizol reagent (Life Technologies Corporation, Thermo Fisher Scientific, Waltham, MA, USA) procedure which has been previously described in our studies (Baloglu et al, 2014d;Çelik Altunoğlu et al, 2016b;Çelik Altunoğlu et al, 2017;Çelik Altunoğlu et al, 2018). Absorbance values were then measured with a spectrophotometer (MultiScanGo, Thermo Fisher Scientific, Waltham, MA, USA) at 260/280 nm wavelengths in order to control the purity and quality of RNA dissolved in DEPC water.…”
Section: Rna Isolation and Real Time Pcr Analysismentioning
confidence: 99%